Exercise induced atrio-ventricular (AV) block during nuclear perfusion stress testing: a case report - Filippo Maria Sarullo; Salvatore Accardo; Paola D’Antoni; Annamaria Martino; Antonio Micari; Vincenzo Pernice; Antonio Castello (Monaldi Archives for Chest Disease, 2016)
Background. Exercise causes enhanced sympathetic discharge and results in physiologic tachycardia. However, in some patients with a diseased conduction system resulting from acute ischemia, exercise can precipitate heart block. Methods and results. In this report we describe a 51 years old male patient with transient advanced degree atrioventricular (AV) block developed during recovery from exercise stress testing, resolved after the administration of atropine. Nuclear perfusion imaging demostrated stress-induced ischemia of the inferior-apical segments, and recovery of perfusion in the images obtained at rest. Coronarography showed critical stenosis of the right coronary artery, which was treated by percutaneous coronary intervention (PCI) and drug eluting stent (DES) deployment. Conclusion. Nuclear myocardial perfusion imaging provides noninvasive evidence that transient ischemia of the infero- apical segment can result in advanced degree AV block in patient with critical severe right coronary disease.